Analisis Pengaruh Pengawasan dan Kemampuan Kerja terhadap Kinerja Karyawan melalui Kualitas Pelayanan Publik di Kantor Bank Jatim Cabang Sumenep - Fara Aryanti Risma Ayu; Hadi Susanto; Sri Mulyani (Universitas 45 Surabaya, 2025)
This study, conducted by Fara Ariyanti Risma Ayu (2025), analyzes the influence of supervision and work ability on employee performance through the mediating role of public service quality at Bank Jatim Sumenep Branch. Employing an explanatory research design with a quantitative approach, the study involved a sample of 86 respondents and used SmartPLS for data analysis. The objectives were to: (1) describe supervision, work ability, public service quality, and employee performance; (2) examine the direct and indirect effects of supervision and work ability on performance, with public service quality as a mediator. Findings show that supervision has a positive but insignificant direct effect on employee performance (original sample = 0.024; p = 0.749), while it has a positive and significant impact on public service quality (0.293; p = 0.000). Work ability significantly influences both public service quality (0.586; p = 0.000) and employee performance (0.316; p = 0.000). Public service quality itself significantly affects employee performance (0.624; p = 0.000). Indirectly, supervision positively and significantly influences employee performance through public service quality (0.183; p = 0.000), as does work ability (0.365; p = 0.000). In conclusion, although direct supervision does not significantly impact employee performance, it contributes through its strong influence on service quality. Work ability is shown to be a crucial factor, both directly and indirectly, in enhancing performance. These findings emphasize the importance of improving service quality as a strategic mediating factor in boosting employee outcomes within the banking sector